Investigation of cleat and micro-fracture and its aperture distribution in the coals of different ranks in North China: Relative to reservoir permeability - Huang, Qiang; Du, Zhigang; Liu, Hewu; Niu, Qinghe; Fang, Huihuang; Yang, Jinyang; Lou, Minghang (Frontiers in Earth Science, 2023)
The apertures of cleats and micro-fractures in coal play an important role in the permeability of the coal bed. In this study, optical microscopy and scanning electron microscopy were used to investigate the morphology of cleats and micro-fractures and their apertures, distribution of minerals, and matrix/fracture interactions. The neighboring mineralized and unmineralized cleats suggest the possibility of multi-stage evolutionary processes of cleat formation during the coalification process. The micro-fracture distribution of coals is closely related to their components, including organic macerals and inorganic minerals. Micro-fractures are prone to developing at the junction surface of organic macerals or the surface of organic and inorganic minerals. A mineral-genetic micro-fracture can be classified as an intra-crystal micro-fracture, an extra-crystal micro-scale fracture, or a grain-edge micro-scale fracture. Compared with the low- and middle-ranking coals, cleat and micro-scale fractures in high-ranking coal are usually filled with carbonate minerals and clay minerals. Statistical analysis reveals that the aperture distribution of cleat and micro-fracture in coal shows a log-normal distribution. The aperture of cleat and micro-fracture shows a decreasing trend with increase in coal rank. For low-ranking coal, cleats contribute more to the permeability than micro-fractures. However, for the middle- and high-ranking coals, the contribution of cleats and micro-fractures to the coal reservoir permeability will be close. As the rank of coal increases, the degree of cleat contribution to reservoir permeability decreases, while the degree of micro-fracture contributing to the reservoir permeability increases. Possible reasons for the extremely low reservoir permeability in China may be the following: 1) subsurface cleats and micro-fractures close their apertures significantly due to the in situ geo-stress or 2) cleats and micro-fractures have better permeability in the geological history, which makes the precipitation of minerals decrease the coal reservoir permeability. Therefore, the acid solvent (e.g., HAc, HCl, and HF) added to the drilling or hydraulic fracturing fluid or the geo-stress relief technologies may be an effective way of enlarging the cleat or micro-fracture aperture and enhance the reservoir permeability for coalbed methane production.